An experimental evaluation of thermoelectric generator performance under cyclic heating regimes - O'Shaughnessy, Seamus (My University, 2022)
Thermal cycling is known to adversely affect the performance and lifespan of thermoelectric generators (TEGs) yet has received limited attention to date. The current study experimentally investigates the effect of thermal cycling on the performance of twelve nominally identical TEG modules. Six samples were subjected to the same thermal cycle profile with an average heating time of 154 s to examine the variation in their outputs. The maximum cycling temperature was varied between 170 °C and 190 °C for a further six samples to investigate the effect of maximum set-point temperature on performance. Degradation in performance was exhibited by all modules, with maximum power outputs between 28% and 57% of pre-cycling values and a decrease in the dimensionless figure of merit ZT of 21% to 56% upon cessation of cycling. Sudden ‘breakdowns’ or significant reductions in output power were observed for all TEGs, accompanied by increased electrical resistance, which is indicative of internal damage to the modules arising from the formation of micro-cracks at the interface between the semiconductor thermocouples and electrically conductive material. The rate of degradation post-‘breakdown’ appeared to be influenced by the maximum set-point temperature, with more rapid decreases observed for increasing temperatures.
PUBLISHED
Keywords: Thermal cycling; Thermoelectric generators; Smart & Sustainable Planet